Screening for Chlamydia trachomatis: a systematic review of the economic evaluations and modelling. Issue 3 (26th May 2006) - Roberts, T E; Robinson, S; Barton, P; Bryan, S; Low, N
Abstract : Objective: To review systematically and critically, evidence used to derive estimates of costs and cost effectiveness of chlamydia screening. Methods: Systematic review. A search of 11 electronic bibliographic databases from the earliest date available to August 2004 using keywords including chlamydia, pelvic inflammatory disease, economic evaluation, and cost. We included studies of chlamydia screening in males and/or females over 14 years, including studies of diagnostic tests, contact tracing, and treatment as part of a screening programme. Outcomes included cases of chlamydia identified and major outcomes averted. We assessed methodological quality and the modelling approach used. Results: Of 713 identified papers we included 57 formal economic evaluations and two cost studies. Most studies found chlamydia screening to be cost effective, partner notification to be an effective adjunct, and testing with nucleic acid amplification tests, and treatment with azithromycin to be cost effective. Methodological problems limited the validity of these findings: most studies used static models that are inappropriate for infectious diseases; restricted outcomes were used as a basis for policy recommendations; and high estimates of the probability of chlamydia associated complications might have overestimated cost effectiveness. Two high quality dynamic modelling studies found opportunistic screening to be cost effective but poor reporting or uncertainty about complication rates make interpretation difficult. Conclusion: The inappropriate use of static models to study interventions to prevent a communicable disease means that uncertainty remains about whether chlamydia screening programmes are cost effective or not. The results of this review can be used by health service managers in the allocation of resources, and health economists and other researchers who are considering further research in this area.